Synergistic effects of 6-shogaol and hyperthermia on ACHN renal cancer cells: modulation of ROS and heat shock pro-teins in cancer therapy - Ahn, Chae Ryeong; Baek, Seung Ho (Frontiers in Pharmacology, 2025)
IntroductionRenal cancer is known for its aggressive progression and resistance to standard treatments, underscoring the need for novel therapeutic strategies. This study explores the potential of combining 6-shogaol (6-SHO), a bioactive compound derived from ginger (Zingiber officinale), with hyperthermia to enhance anticancer efficacy in ACHN renal cancer cells.MethodsACHN cells were treated with 6-SHO and exposed to hyperthermic conditions. We evaluated the combined effects on apoptosis, cell cycle arrest, and cell proliferation, as well as the role of reactive oxygen species (ROS) and heat shock proteins (HSPs) in mediating these responses.ResultsThe combination of 6-SHO and hyperthermia significantly increased apoptosis, induced G2/M phase cell cycle arrest, and reduced cell proliferation more effectively than either treatment alone. ROS played a critical role in these effects, with modulation of HSPs and heat shock factor 1 (HSF1) further disrupting cancer cell survival mechanisms.DiscussionThese findings highlight the synergistic potential of 6-SHO and hyperthermia as a novel therapeutic approach in renal cancer treatment, supporting the need for further research and clinical evaluation.